(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2023)
This paper explores the tangible and intangible art heritages of Chitlang, also known as Chitrapur is an ancient historical route. Before the 18th and early 19th centuries, this was the only route thriving with life. In those days, it used to be a roadway that would never sleep. Today it remains isolated and discarded despite being rich in both tangible and intangible historicity that goes back to the Dwāpara-yuga (Mahabharata period). There are innumerable relics and the inhabitants who claims to be the descendants of the Gopala dynasty of Nepal. There are few books available on Chitlang written by local scholars, but they lack focus on art heritages. This article attempts to throw some light on the tangible heritages and the intangible tales associated with Chitlang/Chitrapur. The methodology is qualitative in nature and based on historicity of Chitlang.